FGFR3 and TP53 mutations in a prospective cohort of Belarusian bladder cancer patients - Smal, M.P.; Rolevich, A.I.; Polyakov, S.L.; Krasny, S.A.; Goncharova, R.I. (Experimental Oncology, 2014)
Aim: The aim of this study was to determine the frequencies of FGFR3 and TP53 mutations in a prospective cohort of 150 bladder cancer patients and to assess the relationship between their mutational status and clinicopathological variables. Materials and Methods: The FGFR3 and TP53 mutations were detected by the SNaPshot method and PCR-single-strand conformational polymorphism analysis followed by DNA sequencing. Results: The activating FGFR3 mutations were found in 71 (47.3%) whereas TP53 mutations were observed in 31 (20.7%) urothelial carcinomas. FGFR3-mutant tumors significantly correlated with lower tumor stage and grade, papillary form of bladder cancer and the absence of metastases while TP53-mutant tumors were strongly associated with higher tumor stage and grade as well as the presence of metastasis. We also found significant inverse correlation between FGFR3 mutations and TP53 alterations in urothelial carcinomas (p=0.03). Four possible genotypes were observed in the whole studied cohort, namely FGFR3mut/TP53wt (41.3%), FGFR3wt/TP53wt (38%), FGFR3wt/TP53mut (14.7%), and FGFR3mut/TP53mut (6%). Tumors with FGFR3wt/TP53wt genotype comprised the subgroup, in which all stages and grades were equally distributed. Conclusions: Our findings confirm the alternative role of FGFR3 and TP53 mutations in the development of bladder cancer. Together these two genetic markers are attributed to 62% of the tumors studied. Tumors with both wild type genes included urothelial carcinomas of all stages and grades and may develop through another genetic pathway. To elucidate complete molecular profile of bladder tumors further additional studies are needed. Key Words: bladder cancer, FGFR3 mutation, TP53 mutation, tumor genotype.